Cover Crop Management in a Sauvignon Blanc/Ramsey Vineyard in the Semi-Arid Olifants River Valley, South Africa. 3. Effect of Different Cover Crops and Cover Crop Management Practices on the Organic Matter and Macro-Nutrient Contents of a Sandy Soil - Fourie, J.C.; Agenbag, G.A.; Louw, P.J.E. (South African Journal of Enology and Viticulture, 2016)
The trial was conducted over a period of ten years (1993/94 to 2002/03) on a sandy soil in a Sauvignon blanc/Ramsey vineyard near Lutzville (31o35’S, 18o52’E), situated in the semi-arid Olifants River Valley of the Western Cape. Fourteen treatments, consisting of three cereals and four legumes, managed according to two cover crop management practices, were included. One management practice consisted of cover crops which were sown annually. Full surface post-emergence chemical control was applied before bud break and again when the berries reached pea size (BB). The second management practice consisted of cover crops which were sown biennially. Post-emergence chemical control was applied to the vine row before bud break and full surface control was applied when the berries reached pea size (AB). From 1999/2000 to 2002/03 the cover crops were sown annually, while the full surface post-emergence control applied at the end of November (berries at pea size) was advanced to mid-October. Two treatments in which Avena sativa L. v. Saia (‘Saia’ oats) and Vicia dasycarpa Ten. (grazing vetch) were sown annually, controlled mechanically in the work row and chemically in the vine row from bud break to harvest (MC), were also applied. These treatments were compared to a control, in which no cover crop was sown and MC was applied. A treatment in which no cover crop was sown and BB was applied (weedchem), was also included. After five years (1997/98), the soil organic matter (SOM) in the 0-150 mm soil layer of the BB and AB treatments of grazing vetch was significantly higher than that of the control and weedchem. During March 2003, the SOM content in the 0-600 mm soil layer of grazing vetch (AB), as well as the 0-150 mm soil layer of Ornithopus sativus L. v. Emena (pink Seradella) (AB) and Secale cereale L. v. Henog (rye) (BB), was significantly higher than that of the control and weedchem. The total inorganic N concentration (TIN) of pink Seradella (BB) was the highest in the 0-150 mm soil layer during the full bloom stage of the grapevines in 1995/96 and significantly higher than that of the other treatments in the 150-300 mm soil layer. The TIN measured in the AB treatments of grazing vetch and pink Seradella as measured after the grapevine harvest (1995/96), was significantly higher than that of the control, weedchem and cereal treatments in the 0-300 mm and 0-150 mm soil layers, respectively. The TIN in the 0-150 mm soil layer of the legumes was, with the exception of pink Seradella (BB), significantly higher than that of the control, weedchem and the BB treatments of the cereals during March 2003. The TIN in the 150-300 mm soil layers of the AB treatments of pink Seradella and the two Medicago truncatula Gaertn. varieties, namely, Parabinga and Paraggio, was significantly higher than that of the control, weedchem and the grain treatments. Potassium concentrations in the 0-150 mm soil layer of the two pink Seradella treatments, the AB treatment of rye, Medicago truncatula Gaertn. v. Paraggio and grazing vetch, as well as the 150-300 mm soil layer of grazing vetch (BB) and pink Seradella (BB), were significantly higher than that of the control, weedchem and ‘Saia’ oats (MC) during March 1997.